MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) MATA PELAJARAN IPS POKOK BAHASANKENAMPAKAN ALAM DAN BUDAYA DI KELAS IV SD NEGERI 055988 GUNUN - SAHPUTRA, EDI (Unversitas Katolik Santo Thomas, 2018)
This study aims to describe the study of Classroom Action Research(PTK) using Student Team Achievement Divisions (STAD) learning model in IPSsubjects in class IV SD Negeri 055988 Gunung Ambat. The research approachused is quantitative and qualitative approach, with the subject of research that isthe fourth grade students of SD Negeri 055988 Gunung Ambat which amounts to31 students. Data collection techniques used are observation and test.The results of the research on the first cycle obtained the number ofteacher observation points as much as 28 with a percentage of 56%. Observationof student activity obtained by the number of points as much as 24 withpercentage 48% and many complete student in accordance with value of CriterionComplete (KKM)> 65 is counted 16 student with percentage 51,61%, while manystudent which not finished in other word not reach Criteria Completeness (KKM)<65 is as many as 15 students with a percentage of 48.38%. The average value ofstudents in the first cycle is 59.83 while the number of students in classicalcompleteness has not reached 75.00% is 51.61%, then continued on cycle II. Inthe second cycle of teacher activity observation results obtained the number ofteacher observation points as much as 39 percentage 78%. Observation of studentactivity obtained by the number of points as much as 38 with percentage 76% andmany complete student in accordance with value Criteria Completeness (KKM)>65 is as many as 27 student with percentage 87%, while many student which doesnot complete in other word does not reach Completeness Criterion KKM) <65 isas many as 4 students with 12.90% percentage. Based on the data analysis, it isconcluded that the implementation of Student Team Achievement Divisions(STAD) learning model on IPS lesson with the subject of natural and culturalappearance in class IV SD Negeri 055988 Gunung Ambat Learning Year2017/2018 has good categorization and learning outcomes increase.The limitation of this study is the Student Team Achievement Division(STAD) model of learning is a model that creates a comfortable learningenvironment for students, so that teachers creativity is required in conveyinglearning.